(untitled) (Práxis Educativa, 2022)
Assemblage thinking has exploded in policy research, especially among scholars working in the policy mobilities field who are seeking to harness the potential of an assemblage approach to understand how policies move, mutate and manifest in increasingly transnational contexts. The ubiquity of assemblage, however, does not always render it clear, with the concept being variously defined and sometimes lacking conceptual strength and explanatory power. This paper seeks to conceptualize and defend an assemblage approach to policy analysis. By synthesizing core threads from existing literature, it identifies three theoretical and conceptual foundations central to a ‘policy assemblage’ approach: (1) relations of exteriority and emergence; (2) heterogeneity, relationality and flux; and (3) attention to power, politics and agency. Together, these foundations signal a coherency to assemblage thinking and suggest an assemblage approach has powerful potential, allowing researchers to see and explain things in ways that many established traditions in policy research do not. By identifying foundations and offering examples of how each might be mobilized, the paper provides the beginnings of a framework for policy assemblage research not previously articulated in a systematic form, thus inviting further discussion about what it means to undertake policy assemblage research. Keywords: Assemblages. Public policy. Mobility. Power.